2018
DOI: 10.1155/2018/3702740
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir-Based Highly Active Antiretroviral Therapy Is Associated with Superior CD4 T Cells Repopulation Compared to Zidovudine-Based HAART in HIV 1 Infected Adults

Abstract: Tenofovir-based highly active antiretroviral therapy (HAART) is one of the preferred first-line therapies in the management of HIV 1 infection. Ghana has since 2014 adopted this recommendation; however there is paucity of scientific data that reflects the safety and efficacy of the tenofovir-based therapy compared to zidovudine in the Ghanaian health system. This study sought to assess the comparative immune reconstitution potential between tenofovir and zidovudine-based HAART regimens, which includes lamivudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(71 reference statements)
2
7
0
Order By: Relevance
“…We detected a statistically significant, but clinically small, improvement in mean renal function after 6 months of TDF use among 476 ART-naïve patients initiating TDF-based first line ART after July 1, 2016. While some studies outside of Africa have found renal toxicity in PLWH on TDF(1)(3)(4), our findings are in agreement with most of the studies from Africa and outside of Africa that have reported TDF to be associated with good clinical outcomes and found to have few side effects in healthy patients(9)(13)(14)(15)(16)…”
Section: Discussionsupporting
confidence: 91%
“…We detected a statistically significant, but clinically small, improvement in mean renal function after 6 months of TDF use among 476 ART-naïve patients initiating TDF-based first line ART after July 1, 2016. While some studies outside of Africa have found renal toxicity in PLWH on TDF(1)(3)(4), our findings are in agreement with most of the studies from Africa and outside of Africa that have reported TDF to be associated with good clinical outcomes and found to have few side effects in healthy patients(9)(13)(14)(15)(16)…”
Section: Discussionsupporting
confidence: 91%
“…A retrospective cohort study conducted by Ayele, Jarso & Mamo (2017) for two years in Ethiopia showed that the TDF regimen had better immune improvements. A prospective study conducted by Badii & Buabeng (2018) in Ghana also showed that patients taking TDF ARVs had a higher CD4 cell increase compared to those using ZDV.…”
Section: Discussionmentioning
confidence: 95%
“…HAART has been associated with a higher CD4 T cells recovery rate compared with non–HAART-based antiretroviral therapy with zidovudine through reduced chronic immune activation, cytolysis, cytotoxic viral proteins, and an increase in thymic function. 14 - 17 Previous reports have suggested that protease inhibitors contained in HAART regimens may be effective in controlling KS independently of immune reconstitution. Protease inhibitors have shown pleiotropic effects having a direct effect on angiogenesis and tumor growth and on human herpesvirus type 8 replication, by targeting the proteasomes and matrix metalloproteinases MMPS and blocking the production of cytokines.…”
Section: Discussionmentioning
confidence: 99%